2022-RA-1641-ESGO The impact on body image and quality of sexual life of transvaginal natural orifice transluminal endoscopic surgery (vNOTES) in women with high genetic risk of female cancers. (20th October 2022) - Caretto, Marta; Massimello, Francesca; Giannini, Andrea; Simoncini, Tommaso
Abstract : Introduction/Background: Women carrying a mutation in BRCA 1 or BRCA 2 genes face complex decisions regarding strategies for managing their increased breast and gynecologic cancer risk. Prophylactic mastectomy in high genetic risk of female cancers could severely affect body esteem decreasing sexual satisfaction. Risk-reducing bilateral salpingo-oophorectomy (RRBSO) through minimally invasive technique has been shown to reduce the risk of ovarian cancer. Recent evidence has suggested that women with BRCA 1 gene mutations may have an increased risk of uterine serous carcinomas. A new minimally invasive technique, Transvaginal Natural Orifice Transluminal Endoscopic Surgery (vNOTES), allows access to the peritoneal cavity through the vagina without skin incisions. Methodology: From June 2021 to February 2022, women carrying a mutation in the BRCA 1 gene, with a history of previous bilateral mastectomy and underwent hysterectomy and RRBSO using vNOTES technique were studied prospectively. We administered validated tools as Female Sexual Function Inventory (FSFI) and Body Image Scale (BIS) to evaluate the impact on cosmetic, psychological and sexual domains. Results: 10 women carring BRCA 1 gene mutation and undergoing vNOTES technique for hysterectomy and RRBSO were enrolled. The mean age was 47 years (range 34–50). 4 (40%) patients had a history of breast cancer and they underwent contralateral prophylactic mastectomy. The mean pain assessment after gynecologic surgery was 2.1 (range 0–5). The complete exploration of the abdomen with peritoneal biopsies were performed in all (100%) cases. 6 (60%) women were high concern with body image. Sexual function decreased progressively with age, but FSFI scores in lubrication, orgasm and pain did not have a statistically significantly change after vNOTES surgery. Conclusion: Risk-reducing surgery may result in changes to patients'appearance. If prophylactic breast surgery severely affects women body esteem, vNOTES for gynecologic prophylactic surgery has the potential to improve surgical experience, provide good long-term functional and cosmetics outcomes.